A Landscape Study of Sediment Formation and Transport in the Urban Environment - Ilia Yarmoshenko (Atmosphere, 2020)
Background: Sediment deposition in the urban environment affects aesthetic, economic, and other aspects of city life, and through re-suspension of dust, may pose serious risks to human health. Proper environmental management requires further understanding of natural and anthropogenic factors influencing the sedimentation processes in urbanized catchments. To fill the gaps in the knowledge about the relationship between the urban landscape and sedimentation, field landscape surveys were conducted in the residential areas of the Russian cities of Ekaterinburg, Nizhniy Novgorod, Rostov-on-Don, Tyumen, Chelyabinsk, and Murmansk. Methods: In each city, six elementary urban residential landscapes were chosen in blocks of multi-story apartment buildings typical for Russian cities. The method of landscape survey involved delineating functional segments within the elementary landscapes and describing each segment according to the developed procedure during a field survey. Results: The complexity of sedimentation processes in the urban environment was demonstrated. The following main groups of factors have significant impacts on sediment formation and transport in residential areas in Russian cities: low adaptation of infrastructure to a high density of automobiles, poor municipal services, and bad urban environmental management in the course of construction and earthworks. Conclusion: A high sediment formation potential was found for a considerable portion of residential areas.